Nano-ZrO2 filled high-density polyethylene composites: Structure, thermal properties, and the influence γ-irradiation. (January 2020) - Nabiyev, A.A.; Olejniczak, A.; Pawlukojc, A.; Balasoiu, M.; Bunoiu, M.; Maharramov, A.M.; Nuriyev, M.A.; Ismayilova, R.S.; Azhibekov, A.K.; Kabyshev, A.M.; Ivankov, O.I.; Vlase, T.; et al.
Abstract: High-density polyethylene (HDPE) composites with different amounts of ZrO2 nanoparticles (1–20 vol%) were prepared by high-pressure thermal pressing. The effect of γ-irradiation on their structural and thermal properties was investigated using small-angle neutron scattering (SANS), X-ray diffraction (XRD), Raman spectroscopy, infrared spectroscopy, differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). SANS analysis confirmed good dispersion of the nanoparticles in HDPE matrix. Upon exposure to γ-radiation only small changes in the lattice parameters and the crystalinity degree occurred for both HDPE and the nanocomposities. More significant changes for irradiated HDPE were observed in DSC-derived parameters, including the decrease in the melting point, and increase in crystalinity degree. This trend was even more pronounced for the nanocomposities. A possible explanation assuming resonant enchantment of polymer chain scission in the presence of ZrO2 nanoparticles is discussed. The extent of radiation-induced oxidation was essentially the same for pure HDPE and the nanocomposities, suggesting that the process is diffusion controlled. The thermal stability of the irradiated composites was somehow higher than that pure HDPE. Highlights: HDPE composites with different amounts of ZrO2 nanofiller prepared by high-pressure thermal pressing. Good dispersion of the ZrO2 nanoparticles obtained while preserving the crystalline structure of the HDPE matrix. Absence of a diffusion region between the filler particles and the polymer matrix confirmed by SANS. Influence of γ-irradiation on the structural and thermal properties of HDPE and HDPE+%ZrO2 nanocomposites was investigated. HDPE+%ZrO2 nanocomposite exhibited excellent thermal and thermo-oxidative stabilities.